The Influence of Organizational Citizenship Behavior and Organizational Culture on Employee Performance with Organizational Commitment as an Intervening Variable (North Medan BPJS Employment Branch Office) - Rahman, Khainur; B, Mesra (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This research aims to determine the influence of Organizational Citizenship Behavior (OCB) and Organizational Culture on Employee Performance with Organizational Commitment as an Intervening Variable. The population of this study was 75 employees and the entire population was used as a sample. The data analysis technique uses path analysis with the help of the smart PLS program. The research results show that OCB has a direct and indirect effect on employee performance. Organizational culture has a positive but not significant effect on employee performance, while an indirect influence, namely through organizational commitment, organizational culture has a significant and significant effect on employee performance at the BPJS Employment North Medan Branch office.